Hidden Hazards in The Pandemic Era of COVID-19 - Illegal Immigration - Pawel LUBIEWSKI (Communications of International Proceedings, 2021)
Contemporary dimension of illegal immigration is of universal nature and concerns modern states, not only the European ones, which have to deal with a significant influx of external immigration. Migrations, apart from their undeniable benefits, generate, to various extents, threats directed towards social and public security in the country of destination. Currently, countries are facing the problem of effective protection against social security dangers in the form of pandemic origin. In such a context, immigrants who stay illegally, permanently hiding from the institutions of the state of residence, become a serious challenge. The purpose of the article is to show that the in the sphere of state responsibility, a community appears which functions in hiding from the state, thus making it impossible to activate any anti-epidemic mechanisms.. An analysis of illegal immigration data in the EU shows that these are large communities. This situation makes illegal immigrant communities not only exposed to epidemiological threats, but also their source. As a consequence, this has a negative impact on the level of social security of the country of residence, where illegally staying foreigners, who are not able to be monitored by the state and interacting with local communities, become a potential source of an epidemic threat whose mechanisms of state control.
Keywords: Pandemic; Covid-19; Illegal Immigration; Social Security; Healthcare Security